ANALISIS PROSES PERENCANAAN DAN PELAKSANAAN ANGGARAN PADA DINAS PARIWISATA DAN EKONOMI KREATIF KOTA PALU - Rustam, Rustam (Katalogis, 2016)
This research is aimed to analyze the process of budget planning and implementation in The DepartmentÂ  ofÂ  Tourism and Creative Economy, Palu City. It is a descriptive qualitative and selects 4 (four) financial managers as its main respondents. The result indicates that the process of budget planning in The Department of Tourism anD, Renja-SKPD, KUA, PPAS, RKA-SKPD, and APBD, which are compiled into a budget implementation document/DPA. However, budget allocation for each program is disproportional and disregards the procurement standard analysis. Moreover, budget implementation has been executed based on the regulation and yet, is not supported by qualified human resources, who have knowledge of financial management. Fund disbursement is often delayed because of waiting for the provision of funds letter/SPD and there is also a delay in money supply process/GU because the financial report is not handed to the treasure on time.